Postoperative mortality following hip fracture surgery in older adults: a single-center retrospective study in the context of Taiwan’s transition to an aged society - Kuang-Ting Tsai; Ting-Gang Guo; Wen-Tien Wu; Ru-Ping Lee; Ting-Kuo Yao; Ing-Ho Chen; Jen-Hung Wang; Kuang-Ting Yeh (Scientific Reports)
Abstract As societies age, understanding the impact of comorbidities on postoperative outcomes following hip fracture surgery becomes increasingly critical. This single-center retrospective study examines the evolving risk factors for postoperative mortality following hip fracture surgery among older adults in Taiwan during its transition to an aged society. We analyzed data from 1,545 patients aged over 65 years who underwent hip fracture surgery at Hualien Tzu Chi Hospital between 2011 and 2020, comparing outcomes before and after 2018—the year Taiwan officially became an aged society. The overall one-year postoperative mortality rate was 6.0%. Significant predictors of increased mortality included advanced age, male sex, ORIF surgical approach, hepatic disease, coronary artery disease, and notably, in-hospital complications such as aspiration pneumonia and UGI bleeding. Our findings revealed that aspiration pneumonia’s impact on mortality intensified significantly in the post-2018 period, highlighting the changing risk profile as Taiwan’s population ages. This study provides critical insights for developing targeted interventions and specialized postoperative care protocols for elderly hip fracture patients, particularly focusing on respiratory care and dysphagia screening. These findings have important implications for healthcare systems adapting to demographic shifts toward super-aged societies.